Islam and Statism: At the intersection of the State of Medina, Modern Statism and the Islamic State - Qureshi, Faisal Ahmad (Advances in Social Sciences Research Journal, 2020)
Since the Arab Spring and the rise of Islamic State, it has become a topic of discussion whether there can be a state based on Islamic principles or values. This paper argues that in modern times there cannot be a state claiming to be Islamic. So the Islamic State of Iraq and Levant or the Islamic State of Iraq and Syria or simply the Islamic State were all misnomers. After the Hijra in 7th century CE, the short lived State of Medina incorporated some of the Islamic principles and it too did not last long enough so as to appreciate the feasibility of a State that was Islamic. However, this paper doesn’t deny the fact that the States cannot espouse Islam as a directive principle in their state policy or declaration of Islam as the state religion. Nonetheless, it is argued that no state can be Islamic post the peace of Westphalia (1648). Therefore, in the 21st century there cannot be any actualization of any Islamic State unless the postcolonial history is normatively challenged. The so-called Islamic state that emerged in Syria & Iraq was a coalition of rebel forces and Mujahideen groups that tried to form a caliphate based on Islamic socio-politico and economic principles, however a futile attempt. For any new Islamic State or a caliphate to emerge, the notion of Westphalian demarcation of boundaries stands as the greatest challenge against it.